FACTORS AFFECTING CRYPTOCURRENCY ADOPTION BASED ON UTAUT2 MODEL: A CASE OF MALAYSIA - YOON , YEONG CHOW (2020)
The advancements in financial technologies are growing rapidly and the most recent innovation is the blockchain-powered cryptocurrencies. As a developing country that has achieved one of the highest financial inclusion rates among the worldwide middle-income countries, Malaysian government demonstrates a favorable attitude towards cryptocurrency. Motivated by the global expression of interests around cryptocurrency, there is a substantial body of literature on cryptocurrency in the domain of information technology, economics, and laws. However, the literature does not present sufficient research cases on cryptocurrency adoption behavior at the individual level and more specifically there is almost absence of relevant research in Malaysia.